Development of noise risk assessment (NRA) and Management System - Asok Kumar, Kirubalini; Fauzan, Nur Syafiqah; Widia, Mirta; Sukadarin, Ezrin Hani; Man, Nor Liyana; Mohd Ibrahim, Mohd Ikhwan (2023)
Noise has become an occupational hazard for workers. Many studies proved that occupational noise-related issues still exist even though thorough inspection, observation, implemented control measures, and medical examinations were carried out. This study focused on the development of a Noise Risk Assessment and Management System based on Industry Code of Practice (ICOP) for Management of Occupational Noise Exposure and Hearing Conservation 2019, Occupational Safety and Health (Noise Exposure) Regulation 2019 and Guidelines on Management of Occupational Noise-Related Hearing Disorder 2021. The system was developed by using Microsoft Access. Two industry experts reviewed and validated the ready system to ensure the content was relevant and complied with the relevant legal requirements and their applicability in industries. The selected experts were among the competent noise risk assessor and safety and health manager. The System Usability Scale (SUS) test and System Functionality and Capability Scale Assessment form were used to validate and verify the system. The SUS score indicates 75.5, which is graded as B. It shows that the system can be used in industry with some improvements that should be made. At the end of this research, a successful Noise Risk Assessment and Management System has been developed to be used in industries